1990
DOI: 10.1111/j.1348-0421.1990.tb00995.x
|View full text |Cite
|
Sign up to set email alerts
|

Pili of Aeromonas hydrophila: Purification, Characterization, and Biological Role

Abstract: Aeromonas hydrophila (Ae6) has 2 morphologically distinctive kinds of pili. One appeared rigid, channeled, and straight with a diameter of 9 nm (Ae6-R pili). The other looked flexible, wavy, and having helical structure with a diameter of 7 nm (Ae6-W pili). Ae6-R pili were purified and characterized.The pili consisted of a subunit protein with a molecular weight of 18 kDa as estimated by SDS-PAGE, and contained 42.3% hydrophobic amino acids and one cysteine residue.The pilus was solubilized to 18 kDa subunit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 34 publications
(39 reference statements)
2
31
0
Order By: Relevance
“…sobria strain BC88, adherence to the intestinal cell line (Henle 407) and intestinal tissue was also not significantly different for the wild type and for the tapA mutant strain. Since type I and Bfp pili are the predominant pilus types seen on these bacterial strains (17,30), this result may not be entirely unexpected. Experiments aimed at visualizing Tap pili on the bacterial cell surface by IEM were not successful, despite the growth of A. veronii bv.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…sobria strain BC88, adherence to the intestinal cell line (Henle 407) and intestinal tissue was also not significantly different for the wild type and for the tapA mutant strain. Since type I and Bfp pili are the predominant pilus types seen on these bacterial strains (17,30), this result may not be entirely unexpected. Experiments aimed at visualizing Tap pili on the bacterial cell surface by IEM were not successful, despite the growth of A. veronii bv.…”
Section: Discussionmentioning
confidence: 77%
“…IEM with anti-TapA serum could not establish whether any of the filamentous structures were Tap pili and, hence, whether they were missing in mutant strains (data not shown). Previous studies with A. hydrophila isolates have shown that the vast majority of pili on the surface of this species are "short-rigid," type I pili (13,17,28).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they biochemically and functionally resemble pili isolated from clinical strains of A . hydrophila from Japan and Thailand ; these pili did not agglutinate rabbit, human, and guinea pig erythrocytes, and like the straight pili reported here, were comprised of a 17,000-mol wt subunit (14,26). The apparent association of straight pili with strains from diverse geographic locations suggests that this pilus type is expressed by most clinical and environmental strains of A .…”
Section: Discussionmentioning
confidence: 97%
“…More recently, ultrastructural examination ofA. hydrophila and the related species A. sobria have revealed the existence of two types of pilus filaments that could be distinguished by morphologic criteria (13,14). Strains expressing one of these pilus types adhere to the HEp-2 cell line, raising the possibility that the colonization of host epithelial surfaces might be mediated by this pilus type.…”
mentioning
confidence: 99%